The influence of head nurse's leadership behavior with professional identity as an intermediary on nurses' turnover intention (以职业认同为中介护士长领导行为对护士离职意愿的影响) - JIA Minghua (贾明华); WANG Yuena (王岳娜); LIU Jianrong (刘建荣) (Journal of International Translational Medicine Limited, 2022)
Objective To explore the influence of head nurses' leadership behavior with professional identity as an intermediary on nurses' turnover intention. Methods Convenient sampling method was used to conduct a questionnaire survey on general information, hospital leadership behavior assessment scale, professional identity scale, and turnover intention questionnaire among 124 nurses in a tertiary hospital in Xi'an. Results The head nurse's leadership behavior score was(81. 41±10. 08)points, and the pm leadership type accounted for 49. 19% of all nurses; The professional identity score was (104. 76±13. 86) points, and the total mean score of turnover intention was (2. 28±0. 68) points. The head nurse's leadership behavior was positively correlated with professional identity (r=0. 546, P＜0. 01), was negatively correlated with turnover intention (r=-0. 468, P＜0. 01); professional identity was negatively correlated with turnover intention (r=-0. 522, P＜0. 01). Professional identity played a part of the mediating role in the relationship between the head nurse's leadership behavior and turnover intention, and the mediating effect accounted for 44. 68% of the total effect. Conclusion The leadership behavior of head nurses indirectly affects the turnover intention through professional. Hospital managers should pay attention to improving the leadership behavior of head nurses to enhance nurse's professional identity, help reduce nurse's turnover intention and stabilize the nursing team. (目的 探究以职业认同为中介护士长领导行为对护士离职意愿的影响。方法 采用方便抽样法, 选取西安市某三甲医院132名临床护士为研究对象, 采用一般情况调查表、医院领导行为评估量表、职业认同评定量表和离职意愿量表进行问卷调查。结果 护士长领导行为得分为(81. 41±10. 08)分, pm型领导类型最多(49. 19%), 职业认同得分为(104. 76±13. 86)分, 离职意愿的总均分为(2. 28±0. 68)分; 护士长领导行为与职业认同呈正相关(r=0. 546, P＜0. 01), 与离职意愿呈负相关(r=-0. 468, P＜0. 01), 职业认同与离职意愿呈负相关(r=-0. 522, P＜0. 01); 在护士长领导行为与离职意愿关系中职业认同发挥部分中介作用, 中介效应占总效应的44. 68%。结论 护士长领导行为以职业认同为中介间接影响护士离职意愿。医院管理者应重视改善护士长领导行为, 以增强护士职业认同感, 有助于降低护士离职意愿, 稳定护理队伍。)